2008
DOI: 10.1007/s10340-008-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean cultivar on life history parameters of Tetranychus urticae Koch (Acari: Tetranychidae)

Abstract: The two-spotted spider mite, Tetranychus urticae Koch, is a very polyphagous pest with a worldwide distribution. In order to appraise population growth parameters of this pest, samples of two-spotted spider mites were taken from soybean (Glycine max) fields of Moghan region, Iran in June 2007 and are reared on bean plants var. Derakhshan (Phaseolus vulgaris) in a growth chamber. The life table parameters of this pest were calculated on three commercial soybean cultivars (Zane, Hach, and L17) and one hybrid (Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 35 publications
6
50
1
Order By: Relevance
“…Before using the leaves in the experiments, they were checked and cleaned of aphids and other pests if required. We replaced the excised leaves every 4-5 days with fresh corn leaves as described previously (Kuo et al, 2006;Razmjou et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Before using the leaves in the experiments, they were checked and cleaned of aphids and other pests if required. We replaced the excised leaves every 4-5 days with fresh corn leaves as described previously (Kuo et al, 2006;Razmjou et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Citrus rust mite is a key pest in the main citrus producing regions of Brazil and its attack may lead to yield losses as well as aesthetic changes in fruit appearance and reduction in total soluble solids (CHIARADIA, 2001;MORAES & FLECHTMANN, 2008;MENDONÇA & SILVA, 2009). The mite T. mexicanus is a leaf pest of several crops including citrus (PRITCHARD & BAKER, 1955;QUIROS-GONZALEZ, 2000;RAZMJOU et al, 2009;VACANTE, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Host plant species often differ in chemical profiles, thereby affecting host (i.e., herbivore) quality [14]. Many authors have reported on the involvement of secondary metabolites in the interaction between plants and herbivorous pests.…”
Section: Effect Of Host Crop On Tetranychus Urticae Populationmentioning
confidence: 99%